2005
DOI: 10.1080/03093640500199612
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Sitting to Standing after Trans-Femoral Amputation

Abstract: Standing up is an important and common daily activity. It is essential for independence and a prerequisite for walking. Many elderly and many subjects with impairments have problems with transition from sitting to standing. The aim of the present study was to determine whether there was any difference between the characteristics of standing up in trans-femoral amputees and healthy subjects. Five young trans-femoral amputees and five healthy subjects were included in the study. They were asked to stand up. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 25 publications
7
26
0
Order By: Relevance
“…Subjects in these studies took a mean duration to stand up of 1.8 (Kuzelicki et al) and 2.6 (Burger et al) s [2,3]. Cumulatively, the stand durations we observed are slightly shorter than those reported by Burger et al and more similar to those reported by Kuzelicki et al [2,3].…”
Section: Durationsupporting
confidence: 73%
“…Subjects in these studies took a mean duration to stand up of 1.8 (Kuzelicki et al) and 2.6 (Burger et al) s [2,3]. Cumulatively, the stand durations we observed are slightly shorter than those reported by Burger et al and more similar to those reported by Kuzelicki et al [2,3].…”
Section: Durationsupporting
confidence: 73%
“…Larger peak lateral trunk lean and overall range of motion observed here is consistent with other patient populations, such as Parkinson's Disease [19] or hemiparesis [22]. Similarly, transverse trunk rotations were larger with transfemoral amputation, with the largest rotations again occurring toward the intact limb [15,23]. In contrast, uninjured controls had minimal lateral and transverse trunk motion, and small joint moments and powers in the frontal and transverse planes.…”
Section: Discussionsupporting
confidence: 86%
“…These individuals consistently demonstrate weight bearing asymmetries among the lower extremities, with higher loads in the unaffected limb. Persons with unilateral LLA also tend to rely more upon their intact limb during gait [13], and lower-extremity kinetic asymmetries have been observed during sit-to-stand movements [14][15][16]. Yet, despite the upper body's substantial proportion of total body mass Increases in spinal loading have been related to altered movements of the lower back during gait among persons with lower limb amputation, movements which are self-perceived by these individuals as contributing factors in the development of low back pain.…”
Section: Introductionmentioning
confidence: 99%
“…Prostheses replace an amputated part of the body and try to restore the lost body function and decrease the problems with activities and participation. [7][8][9][10][11][12][13][14] Orthoses also influence body functions, such as increased or decreased mobility, pain, decreased muscle strength and so on. 15 The result is improved functioning.…”
Section: Introductionmentioning
confidence: 99%